On the problem of a consistent description of kinetic and hydrodynamic processes in dense gases and liquids - Markiv, B.B.; Omelyan, I.P.; Tokarchuk, M.V. (Condensed Matter Physics, 2010)
For a consistent description of kinetic and hydrodynamic processes in dense gases and liquids the generalized non-Markovian equations for the nonequilibrium one-particle distribution function and potential part of the averaged enthalpy density are obtained. The inner structure of the generalized transport kernels for these equations is established. It is shown that the collision integral of the kinetic equation has the Fokker-Planck form with the generalized friction coefficient in momentum space. It also contains contributions from the generalized diffusion coefficient and dissipative processes connected with the potential part of the enthalpy density. Для узгодженого опису кінетичних і гідродинамічних процесів у густих газах і рідинах одержано узагальнені немарківські рівняння для нерівноважної одночастинкової функції розподілу та середнього значення густини потенціальної частини ентальпії. Розкрито внутрішню структуру узагальнених ядер переносу даних рівнянь. Показано, що інтеграл зіткнення кінетичного рівняння має структуру Фоккера - Планка з узагальненим коефіцієнтом тертя в імпульсному просторі. Він також містить вклади від узагальненого коефіцієнта дифузії в просторі імпульсів і дисипативних процесів, пов'язаних із густиною потенціальної частини ентальпії.